2010
DOI: 10.5005/jp-journals-10016-1007
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Pregnancy in a Natural Conception

Abstract: Heterotopic pregnancy is rare in natural conception and most often presents as life threatening emergency like acute abdomen and hemorrhagic shock. In early unruptured stages, it presents nonspecifically, mimicking normal or abnormal pregnancy manifestations. A high index of suspicion and a definitive search for it even after confirming normal intrauterine gestation is needed. This little effort ensures a timely diagnosis and management thus preventing catastrophe. We hereby report a primigravida with unruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Methotrexate, mifepristone, and prostaglandins cannot be used as a result of their putative harmful effects on the viable IUP. 10,11 Considering all treatment possibilities, we recommend to correlate development of serum β-hCG level with clinical findings: reaching zero if the putative IUP did not develop adequately and resulting in abortion or increasing in a remaining intact IUP. 12 Luckily, if diagnosed early, HP has a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate, mifepristone, and prostaglandins cannot be used as a result of their putative harmful effects on the viable IUP. 10,11 Considering all treatment possibilities, we recommend to correlate development of serum β-hCG level with clinical findings: reaching zero if the putative IUP did not develop adequately and resulting in abortion or increasing in a remaining intact IUP. 12 Luckily, if diagnosed early, HP has a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…They are safe agents with no risk of systemic toxicity to the remaining gestation. Methotrexate, mifepristone, and prostaglandins cannot be used as a result of their putative harmful effects on the viable IUP 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…Historically, the prevalence is estimated at 1 in 30,000; however, more recent studies have demonstrated that with pregnancies involving ovulation induction and in vitro fertilization, the incidence has increased to 1 in 100. 1,3 Other investigators estimate the risk of heterotopic pregnancy at 1 in 119, and this number rises to 1 in 45 with embryo transfer. 4 With embryo transfer, the excessive number of embryos causes multiple pregnancies, ectopic pregnancies, and heterotopic pregnancies.…”
Section: Discussionmentioning
confidence: 99%